Driving Mechanisms for Microbial Community Succession and Change of Volatile Flavor Compounds during the Solid-State Fermentation of Black High-Temperature Daqu - DENG Aling, TANG Jie, ZHU Chutian, HUANG Yongguang (Shipin Kexue)
This work employed high-throughput sequencing technology to delve into the mechanism driving microbial community succession during the fermentation of black Daqu used for Jiangxiangxing Baijiu production, and it also applied flavoromics to analyze the change of volatile flavor compounds. Furthermore, this study performed an integrative analysis of the driving mechanisms for microbial community succession and the change of volatile flavor compounds. The results showed that temperature, moisture, and acidity were the key driving factors for microbial community succession. A large accumulation of pyrazines occurred during the transition from the first to the second turnover stage, indicating that this transition might be key to the synthesis and formation of flavor substances in black Daqu. The microbial community structure of black Daqu during the fermentation process was quite different from that of ordinary Daqu. Bacillus and Thermoascus predominated in the microbial community throughout the fermentation process, while biomarkers in different stages showed stage-by-stage succession patterns. It was also found that the bacterial community exerted a significant effect on the fermentation power of black Daqu, while the fungal community was the major contributor to the liquefaction power. For the bacterial community, Oceanobacillus, Virgibacillus and Kropentedtia positively contributed to the synthesis of various flavor compounds such as ethyl decanoate, 2-acrolein, benzyl alcohol, and benzyl alcohol. For the fungal community, Saccharomyces was positively correlated with various pyrazines. This study provides a theoretical basis for understanding the evolution of microbial community characteristics and flavor compounds during the fermentation process of black Daqu, thereby offering new insights into strengthening brewing production and product quality.